2023
DOI: 10.3390/biom13050749
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Iron Concentration in the Human Placenta in Twin Pregnancies

Abstract: Background: Pregnancy significantly increases the demand for iron (Fe) in the female body to facilitate maternal blood volume expansion, placental development, and fetal growth. As Fe flux in pregnancy is significantly influenced by the placenta, the aim of this study was to determine the dependencies between the Fe concentration in the placenta, the infant’s morphometric parameters and the woman’s morphological blood parameters in the last trimester. Methods: The study was conducted on 33 women with multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…Our findings were supported by several studies that found no significant associations between iron exposure and body length/height [25,41] or head circumference [22,23,25]. However, other studies have found positive [7,8,19] or negative [29][30][31] associations between iron exposure and these two anthropometric indicators. Sources of heterogeneity in these studies may include different routes of iron exposure (including diet, iron supplementation, blood, and placenta), different study populations (in some studies, outcomes were measured in children rather than fetal or neonatal), and differences in baseline iron levels in the developed and developing countries studied, such as Sweden and Honduras [29].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings were supported by several studies that found no significant associations between iron exposure and body length/height [25,41] or head circumference [22,23,25]. However, other studies have found positive [7,8,19] or negative [29][30][31] associations between iron exposure and these two anthropometric indicators. Sources of heterogeneity in these studies may include different routes of iron exposure (including diet, iron supplementation, blood, and placenta), different study populations (in some studies, outcomes were measured in children rather than fetal or neonatal), and differences in baseline iron levels in the developed and developing countries studied, such as Sweden and Honduras [29].…”
Section: Discussionsupporting
confidence: 90%
“…These results were further supported by several other studies investigating iron exposure from dietary intake [24], blood [25], and amniotic fluid [26]. Conversely, several studies have suggested potential adverse associations between higher blood or placental iron status and anthropometric indicators [27][28][29][30][31]. Two studies of South Korean women found that higher serum ferritin concentration or dietary iron intake were associated with lower femur length and biparietal diameter [27,28].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation